Fireworks [videorecording (DVD)] - Shinbō, Akiyuki, 1961-; Takeuchi, Nobuyuki; Iwai, Shunji, 1963- (Shout! Factory, 2018)
A girl, who plans to run away from home, finds a crystal ball that has supernatural powers.